Policy actors and human and animal health practitioners’ perceptions of antimicrobial use and resistance in Tanzania: A qualitative study - Frumence, Gasto (J Glob Antimicrob Resist, 2021)
OBJECTIVE: To explore and describe the perceptions of policy actors and practitioners on antimicrobial use and resistance in human and animal health in Tanzania. METHODS: This was an exploratory qualitative study, which involved semi-structured interviews with nine policy makers and 102 practitioners. RESULTS: Improved multisectoral collaboration and coordination among experts from the animal and human sectors, government will, improved infrastructures, existence of public awareness campaigns on appropriate use of antimicrobials and existence of antimicrobial stewardship were identified as strengths for the implementation of National Action Plan on Antimicrobial Resistance (NAP-AMR) in Tanzania. Despite these strengths, insufficient public awareness of AMR, limited community engagement and inadequate human resources were among the reported weaknesses. A number of opportunities for the implementation of NAP-AMR were also reported including the presence of integrated disease surveillance and response strategy in health sector and development of a coordinated surveillance system. Furthermore, the inadequate laboratory capacity and poor resource mobilization were identified as challenges facing the implementation of NAP-AMR. CONCLUSION: The future policies of AMR need to capitalize on the identified strengths and opportunities as well as design interventions to improve public awareness of AMR and community engagement, deployment of adequate human resources and ensure adequate resource mobilization to meet AMR needs.